Moving It Along: A study of healthcare professionals’ experience with ethics consultations - Crigger, Nancy (Nursing ethics, 2017)
Background:Ethics consultation is the traditional way of resolving challenging ethical questions raised about patient care in the United States. Little research has been published on the resolution process used during ethics consultations and on how this experience affects healthcare professionals who participate in them.Objectives:The purpose of this qualitative research was to uncover the basic process that occurs in consultation services through study of the perceptions of healthcare professionals.Design and Method:The researchers in this study used a constructivist grounded theory approach that represents how one group of professionals experienced ethics consultations in their hospital in the United States.Results:The results were sufficient to develop an initial theory that has been named after the core concept: Moving It Along. Three process stages emerged from data interpretation: moral questioning, seeing the big picture, and coming together. It is hoped that this initial work stimulates additional research in describing and understanding the complex social process that occurs for healthcare professionals as they address the difficult moral issues that arise in clinical practice.